The role of uric acid in the pathogenesis of human cardiovascular disease. Issue 11 (23rd January 2013) - Kanbay, Mehmet; Segal, Mark; Afsar, Baris; Kang, Duk-Hee; Rodriguez-Iturbe, Bernardo; Johnson, Richard J
Abstract : Hyperuricaemia is common in subjects with cardiovascular disease, but is not commonly considered a true risk factor. Recent studies suggest that uric acid is biologically active and can stimulate oxidative stress, endothelial dysfunction, inflammation and vasoconstriction. Epidemiological studies have found that uric acid can independently predict the development of hypertension, as well as stroke and heart failure. Experimentally raising uric acid in animals increases blood pressure, and pilot studies suggest that lowering uric acid in humans can reduce blood pressure in hypertensive individuals. Uric acid may also have emerging roles in the pathogenesis of kidney disease, metabolic syndrome and diabetes. More studies need to be performed on the pathophysiology and clinical consequences of hyperuricaemia in cardiovascular disease.